Reversing cold tumors to hot: An immunoadjuvant-functionalized metal-organic framework for multimodal imaging-guided synergistic photo-immunotherapy - Fan, Zhijin; Liu, Hongxing; Xue, Yaohua; Lin, Jingyan; Fu, Yu; Xia, Zhaohua; Pan, Dongming; Zhang, Jian; Qiao, Kun; Zhang, Zhenzhen; Liao, Yuhui (Bioactive materials, 2021)
Immunotherapy assays using immunoadjuvants and tumor antigens could greatly increase the survival rates of patients with malignant tumors. As effective carriers, metal-organic frameworks (MOFs) have been widely utilized in cancer therapy due to their remarkable histocompatibility and low toxicity. Herein, we constructed a multimodal imaging-guided synergistic cancer photoimmunotherapy by employing a specific MOF (MIL101-NH2) as the core carrier; the MOF was dual-dressed with photoacoustic and fluorescent signal donors (indocyanine green, ICG) and immune adjuvants (cytosine-phosphate-guanine sequence, CpG) and named ICG-CpG@MOF. This nanocarrier could passively target the tumor site through the EPR effect and achieve multimodal imaging (fluorescence, photoacoustic, photothermal and magnetic resonance imaging) of the tumor. Synergistic cancer photoimmunotherapy was achieved via simultaneous photodynamic and photothermal methods with 808 nm laser irradiation. ICG-CpG@MOF achieved the GSH-controlled release of immunoadjuvant into the tumor microenvironment. Furthermore, the released tumor-associated antigen along with CpG could induce the transformation of tumor cells from cold to hot by activating the immune system, which significantly enhanced tumor cytotoxicity and achieved high cure rates with minimal side-effects. This strategy utilizing multimodal imaging and synergistic cancer photoimmunotherapy provides a promising approach for the diagnosis and treatment of cancer. [Display omitted] •Tumor microenvironment and light dual-response nanoplatform realize multi-modal imaging-guided cancer photo-immunotherapy.•When light triggers photothermal therapy, the immune system is activated to play a long-acting anti-tumor effect.•Nanoscale MOF could accumulate at the tumor site via the EPR effect and tumor-enhanced micropinocytosis.